Contribution of highly active anti-retroviral therapy to the development of non-alcoholic fatty liver disease with concomitant cardiovascular dysfunction in an obese rat model - Kamau, Festus Maina (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.